Clinical effectiveness of robotic-assisted compared to open or video-assisted lobectomy in Germany: a real-world data analysis - Eichhorn, Martin E.; Bernauer, Eva; Rotärmel, André; Heurich, Manuel; Winter, Hauke (Interdisciplinary cardiovascular and thoracic surgery, 2024)
Despite robotic-assisted thoracic surgery (RATS) lobectomy being on the rise in Europe, the majority of lobectomies in Germany are still performed with an open or thoracoscopic [video-assisted thoracic surgery (VATS)] approach. Empirical evidence in favour of RATS lobectomy is inconsistent. This retrospective cohort study investigates the impact of RATS lobectomy compared with open thoracic surgery (OPEN) and VATS lobectomy on short-term outcomes in Germany using multicentre real-world data.Anonymized routine data from Germany from 2018 to 2020 were retrospectively analysed. These data were provided by 61 German hospitals. Propensity score matching with subsequent generalized linear models was performed for statistical analysis. Additionally, in order to test the robustness of the results, multivariable regression analyses with cluster-robust standard errors were used.A total of 2498 patients with lobectomy were identified: in 1345 patients OPEN, in 983 VATS and 170 a RATS lobectomy was performed. RATS - compared to OPEN and VATS - reduced length of stay (LOS) by 28% or 4.2 days [confidence interval: 2.9; 5.4] and by 13% or 1.6 days [confidence interval: 0.2; 3.0], respectively. The risk of pneumonia was reduced by 5.3 percentage points in the RATS group compared to both OPEN and VATS (P = 0.07/0.01). RATS - compared to an open approach - reduces the risk of blood transfusions by 8.8 percentage points (P < 0.001) and LOS on the intensive care unit (P < 0.001).This study provides strong support that RATS lobectomy outperforms OPEN or VATS lobectomy in terms of hospital LOS, and short-term in-hospital postoperative complications in the real-world scenario in Germany.